ADAPTING TO EVOLVING CONSUMER TRENDS: AN IN-DEPTH ANALYSIS OF STRATEGIC APPROACHES IN MARKETING MANAGEMENT ANDCONSUMER BEHAVIOR - Ari Kristiana; Akbar Nuur Purnama Darma Wahana; Grace Christien Sumakul (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This paper extensively examines strategic approaches in marketing management and consumer behavior to respond to the dynamic shifts in consumer trends adeptly. Drawing from a diverse range of academic literature and industry reports, it elucidates critical theories and frameworks for navigating modern markets' ever-changing landscapes. This analysis includes concepts such as market orientation, data analytics, brand loyalty, and collaborative ventures, which are deemed indispensable for maintaining competitiveness in today's rapidly evolving business environment. Furthermore, the study underscores the importance of agility, adaptability, and innovation in effectively addressing consumers' evolving preferences. Additionally, it delves into the significance of comprehending cross- cultural disparities, harnessing the potential of digital technologies, and embracing sustainability practices to facilitate meaningful engagement with contemporary consumers. Through a comprehensive synthesis of existing literature, this research offers actionable insights and pragmatic recommendations tailored to businesses seeking to flourish amidst the dynamic nature of modern markets.